2008
DOI: 10.1080/00365540701509899
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of adults with pulmonary tuberculosis with and without HIV infection in Nigeria

Abstract: Our aim was to describe the frequency of HIV infection among patients with tuberculosis and compare their characteristics with patients with TB but not infected with HIV. Patients with cough >3 weeks duration attending 8 hospitals in Abuja, Nigeria were screened with smear microscopy and culture and tested for HIV. Chest X-rays were graded by 2 readers. 731 (62%) of 1186 patients had positive cultures and 353 (48%) of these 731 patients were smear positive. 1002 (85%) patients were tested for HIV and 546 (55%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 13 publications
(3 reference statements)
0
32
1
Order By: Relevance
“…Chest radiograph scoring is a relatively insensitive indicator of pulmonary inflammation (21), because it only measures area of lung involvement but not density of consolidation, and yet a positive association with MMP-1 concentration was shown. In support of a central role for MMP-1 in TB pathogenesis, MMP-1 polymorphisms have been linked to the risk of developing TB (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chest radiograph scoring is a relatively insensitive indicator of pulmonary inflammation (21), because it only measures area of lung involvement but not density of consolidation, and yet a positive association with MMP-1 concentration was shown. In support of a central role for MMP-1 in TB pathogenesis, MMP-1 polymorphisms have been linked to the risk of developing TB (29).…”
Section: Discussionmentioning
confidence: 99%
“…A modified chest radiograph scoring system was used ( Figure E1) (21). Cavities were recorded as present or absent.…”
Section: Clinical Scoring Systemmentioning
confidence: 99%
“…Tuberculosis control and prevention programs are based on early diagnosis, followed by rapid identification of drug resistance strains [3]. A study by Lawson reported that multi drug resistant tuberculosis (MDR/TB) has implicated as much as 8% of all cultured specimens which were MDR/TB positive cases as recorded in three states in Nigeria [4]. Potentially, lots of awareness and campaigns have been on to reduce the incidence rate of the disease to the barest minimum, but TB elimination remains a critical massive challenge, due to some critical factors like the emergence and re-emergence of clinical forms of rifampicin and multi-drug-resistant strains [1] The increasing trend of Human Immunodeficiency Virus infection contribute massively towards worsening the health conditions of the subject's affected [1].…”
Section: Introductionmentioning
confidence: 99%
“…[2] [12] Nigeria have the fourth highest burden of tuberculosis (TB) in the world, with an annual incidence of 311 cases per 100,000 population and a mortality rate of 81 per 100,000 population in 2006. [4] [ 13] In Nigeria, about 21% of all TB patients are dually infected with TB and HIV. [3] [4] In 2013 of the estimated 9 million people who developed TB, an estimated 1.1 million (13%) were HIV positive.…”
Section: Introductionmentioning
confidence: 99%
“…[4] [ 13] In Nigeria, about 21% of all TB patients are dually infected with TB and HIV. [3] [4] In 2013 of the estimated 9 million people who developed TB, an estimated 1.1 million (13%) were HIV positive. There were also 360,000 deaths from HIV associated TB equivalent to 25% of all TB deaths, and around 25% of the estimated 1.5 million deaths from HIV/AIDS in the same year.…”
Section: Introductionmentioning
confidence: 99%